2017
DOI: 10.5820/aian.2403.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Religious and Spiritual Practices Among Homeless Urban American Indians and Alaska Natives with Severe Alcohol Problems

Abstract: Engagement in religious and spiritual practices may be protective for homeless individuals with alcohol-related problems. However, little is known in this regard for urban-dwelling American Indians and Alaska Natives (AI/ANs) who have disproportionately high rates of homelessness and co-occurring alcohol use problems. Using secondary data from a nonrandomized controlled study testing a Housing First intervention, AI/AN participants (n = 52) and non-AI/AN participants (n = 82) were compared on demographic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Moreover, some of the participants said that an inauthentic, overly prescriptive, or “pan-Indian” approach would dissuade them from using the app. Our results, as well as prior research, support the value of spiritual and religious practices as a protective factor against alcohol misuse and an aid to recovery among ANAI people [ 57 , 67 - 72 ]. Determining the feasibility of offering relevant options for potential ANAI users, together with exploring mechanisms to enable users to configure this feature themselves, will be a focus of the next phase of research.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, some of the participants said that an inauthentic, overly prescriptive, or “pan-Indian” approach would dissuade them from using the app. Our results, as well as prior research, support the value of spiritual and religious practices as a protective factor against alcohol misuse and an aid to recovery among ANAI people [ 57 , 67 - 72 ]. Determining the feasibility of offering relevant options for potential ANAI users, together with exploring mechanisms to enable users to configure this feature themselves, will be a focus of the next phase of research.…”
Section: Discussionsupporting
confidence: 86%
“…Five studies 31–34 , 35 found TCP participation or interventions to be associated with a lower proportion of self-reported substance use behaviors. Three studies 28 , 36 , 37 found that TCP participation was associated with either fewer days consuming alcohol or fewer alcoholic drinks consumed. One study 33 reported lower substance use odds associated with TCP participation.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also clearly showed the importance of spiritual practices in various life situations such as that done by Wendt et al (2017) concerning spiritual practices among the homeless which found that respondents who were increasingly frequent doing spiritual practices became increasingly less addicted to alcohol. A study by Carr & Kroth (2017) found that spiritual practices such as solah (prayer), fasting, ibadah (acts of devotion) helped a person to get closer to God and this was self-transformation process.…”
Section: Introductionmentioning
confidence: 94%
“…This finding is in line with a study which found that religion and spirituality play a very important role in human life. Religion plays various roles such as it gives peace of mind, gives strength to face the trial of ill-health, assists in self-transformation, builds positive emotions and reduces feelings of depression (Emlet et al 2018;Van de Velde et al 2017;Carr & Kroth 2017;Wendt et al 2017;Van Cappellen et al 2016;Abdullah et al, 2016;Gopal, 2014;Mokhtar & Albaraka, 2016;Hamjah et al2017;Hamjah & Mohd. Arib, 2015).…”
Section: 73mentioning
confidence: 99%